Propuesta de agroturismo para la Finca Buena Vista del Cantón Catamayo, Provincia de Loja. - Acaro Herrera, Segundo Mauricio (2024)
Agro-tourism is a tourist activity that is developed in rural areas, which allows tourists to be in contact with nature and the approach to productive tasks that are performed in the fields. For the development of this project, the general objective was established as: to formulate a proposal for agrotourism in the Finca Buena Vista of the Catamayo canton, Province of Loja, from this general objective two specific objectives are derived, the first is oriented to perform the agrotourism diagnosis of the property, the second is the development of the proposal for agrotourism in the Finca Buena Vista. For the first objective, the techniques used were direct observation, literature review, surveys, SWOT matrix, the comparative and descriptive method and the grid sampling method. For the second objective, the Canvas model was used to generate the proposal. It was determined that the farm has a wide variety of agricultural and livestock products, natural and cultural resources, available land to offer tourism services, little competition, and the study of the potential market shows that tourists are very receptive to agrotourism. Therefore, the farm has the aptitude to develop agrotourism.